PEMBELAJARAN DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) MENGGUNAKAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FLUIDA STATIS - Risma Mamusung; Patricia M. Silangen; Theresje Mandang (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Learning physics means learning about natural concepts, which essentially explain the collection of knowledge in the form of natural phenomena or phenomena, concepts, principles, laws, theories based on logical thinking in accordance eith supporting facts. The purpose of this study was to determine the effectiveness of Learning Through Approach (CTL) using experimental methods to improve the learning outcomes of student physics in material class XI for static liquids in SMA Negeri 1 Tagulandang. This study was a quasi-experimental study using the posttest control group design. The population in this study consisted of students from class XI IPA with a focus on the odd semester 2019/2020, and the sample in this study was carried out at random. These are all samples of IPI with a focus on the odd semester 2019/2020, which are divided into two classes, namely class XI IPA 1 as an experimental class and class XI IPA 2 as a control class. The data in this study are student learning outcomes after treatment. The conclusion of this study is that there are differences in learning outcomes between the experimental class and the control class. This difference is evident from the average of learning outcomes after testing the experimental class at 80.40 and the control class at 70.16, and learning by approach (CTL) using the experimental method efectif in brimg the learning outcomes of students at Tagulandang State High Improve School 1, especially with static fluid material.